An essay on the nature and conduct of the passions and affections : with illustrations on the moral sense - Hutcheson, Francis, 1694-1746 (Hutcheson, Francis, 1694-1746. Works. 2002., 2002)
"Francis Hutcheson is one of the central figures in eighteenth-century moral philosophy. Read widely in Britain, France, Germany, and America, he influenced philosophers ranging from his student Adam Smith to Kant. After the initial reaction to his first major work, Inquiry into the Original of Our Ideas of Beauty and Virtue (1725), Hutcheson took stock of his critics and wrote An Essay on the Nature and Conduct of the Passions and Affections, with Illustrations on the Moral Sense. The first half of the work, the Essay, presents a rich moral psychology built on a theory of the passions and an account of motivation deepening and augmenting the doctrine of moral sense developed in the Inquiry. The Illustrations on the Moral Sense is a brilliant attack on rationalist moral theories and the font of many of the arguments against the motivating power of reason taken up by Hume and used to this day." "Despite intrinsic merits of the Essay on the Nature and Conduct of the Passions and the Illustrations on the Moral Sense, and their vast influence, the original English-language text has until recently been available only in expensive reprint. The Liberty Fund edition makes Hutcheson's seminal work widely available in English in a critical edition collating the first edition of 1728 with Hutcheson's revision of 1742"--Jacket